“CORTE CONSTITUCIONALY ACTUACIONES DE OFICIO. ANÁLISIS DE LA SENTENCIA 1965-18-EP/21” - Calva Peña, Michael Andrés (2025)
The purpose of this research is to provide a brief overview of the history of constitutional control in Ecuador, as well as the historical background of fundamental principles such as the Iura Novit Curia and the Dispositive Principle, concluding by elaborating on the constitutional guarantee called Extraordinary Action of Protection and the functions of the Constitutional Court of Ecuador. The need to include all these aforementioned issues arises after having analyzed the judgment 1965-18-ep/21, which is developed as follows: Silvano Reyes (who will be referred to from now on as the plaintiff), filed an extraordinary action for protection, which in its pertinent part mentions the following: “(...) therefore, ordering the full 9 reparation of the appellant, I ask that you please order the continuation of the Cassation process and that my right to orally justify my appeal be restored, as provided by law and the Constitution before an impartial Court, so that my right of access to justice is protected and not sacrificed for mere formalities.” Reading this, we see that the plaintiff claimed his right to justify the extraordinary appeal for cassation be restored orally. Logically or by doing a quick hermeneutic process it would be possible to know how or within what limits the Constitutional Court should have resolved, the problem that arises next is that the Constitutional Court itself accepts; yes, the extraordinary action of protection and resolves it, but in a different way to that raised by the plaintiff, exceeding its functions and applying figures that are their responsibility as a court, but in a wrong way, that is why the title of this research work and its present development.